The Relationship Between Menopausal Symptoms and Cognitive Function Among Postmenopause Women in Indonesia - Aminah Aminah; Eli Amaliyah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Background : Although memory changes may be a result of menopausal symptoms in healthy individuals, the nature of the relationship between menopausal symptoms and cognitive deficits in the context of postmenopausal women remains unclear. Objective:This study aimed therefore to evaluate the relationship among postmenopausal Indonesian women between distinct menopausal symptoms and the cognitive function. Methods : This study was conducted using a cross-sectional design at two public health centers in Banten, Indonesia. A total of 200 participants were recruited. Data included demographic and clinical information, scores from the Green Climacteric Scale (GCS) for menopausal symptom measurements, and scores from Montreal Cognitive Assessment (MoCA). Multiple regression analyses explored the association between menopausal symptoms and cognitive function. Results: The average age of the sample was 65.6 years (standard deviation: 10.3). Postmenopausal women with cognitive impairment were found to have significantly different month since menopause than postmenopausal women without cognitive decline (p = 0.001). The mean score for anxiety and vasomotor symptoms was greater in women with cognitive decline than in women without cognitive decline (3.42.56 vs. 3.72.69, and 0.810.81 vs. 1.071.0, respectively). Anxiety (B = -0.15, p =0.03) was found to be substantially associated with it. Conclusion: Anxiety was associated with poor cognitive function in postmenopausal women. More nurse-enhanced cognitive training interventions should be developed and modified for testing with Indonesian postmenopausal women.Meskipun perubahan memori mungkin merupakan hasil dari gejala menopause pada individu yang sehat, sifat hubungan antara gejala menopause dan defisit kognitif dalam konteks wanita pascamenopause masih belum jelas.Penelitian ini bertujuan untuk mengevaluasi hubungan di antara perempuan Indonesia pascamenopause antara gejala menopause yang berbeda dan fungsi kognitif.Penelitian ini dilakukan dengan menggunakan desain cross-sectional di dua pusat kesehatan masyarakat di Banten, Indonesia. Sebanyak 200 peserta direkrut. Data termasuk informasi demografis dan klinis, skor dari skala klimakterik hijau (GCS) untuk pengukuran gejala menopause, dan skor dari penilaian kognitif Montreal (MOCA). Analisis regresi berganda mengeksplorasi hubungan antara gejala menopause dan fungsi kognitif.Usia rata-rata sampel adalah 65,6 tahun (standar deviasi: 10.3). Perempuan pascamenopause dengan gangguan kognitif ditemukan memiliki bulan yang berbeda secara signifikan sejak menopause daripada wanita pascamenopause tanpa penurunan kognitif (p = 0,001). Skor rata-rata untuk gejala kecemasan dan vasomotor lebih besar pada wanita dengan penurunan kognitif daripada pada wanita tanpa penurunan kognitif (3.42,56 vs 3.72,69, dan 0,810,81 vs. 1.071.0). Kecemasan (b = -0.15, p = 0,03) ditemukan secara substansial dikaitkan dengannya. Kecemasan dikaitkan dengan fungsi kognitif yang buruk pada wanita pascamenopause. Lebih banyak intervensi pelatihan kognitif yang ditingkatkan perawat harus dikembangkan dan dimodifikasi untuk pengujian dengan perempuan pascamenopause Indonesia.